Elemental analysis of ignimbirite by Raman spectroscopy methods and instrumental neutron activation analysis - Kilic, Ayse Didem; Cakmak, Busra (Pergamon-Elsevier Science Ltd, 2021)
The mineralogy, trace and minor element geochemistry and different color changes of Bitlisignimbirite (eastern Turkey) were measured with Neutron Activation Analysis and Confocal Raman spectrometr methods. From these analyzes, were determined three levels as lower, middle and upper according to texture, color, welded degree, component and chemical differences in Bitlis ignimbrites in study area. The most distinguishing feature observed in black, red and grey color ignimbirite levels are partially mineralogical compositions, fiamme geometry and appearance of different colors. The mineralogical compositions of all levels are plagioclase, feldspar, augite, fayalite, biotite, sanidine, hematite and Fe-Ti oxide (titanomite, ilmenite) minerals. The matrix consists of quartz, anorthoclase, Fe-Ti oxide and sanidine. In addition, the matrix rarely contains glassy and dispersed mineral microliths, apart from intermediate levels of iron oxide/hydroxides. The intermediate levels have higher Fe-Ti oxide composition than others. The hydrous minerals in all ignimbrite levels have been partially replaced by devitrification minerals. The fayalite, which rarely seen in ignimbrites is determined by Raman spectroscopy method in Bitlis ignimbrite. The Raman spectra of different colored ignimbirites obtained using Confocal Raman spectroscopy showed different spectra between 869 and 3062 cm(-1) for the grey, black, and reddish colored ignimbirites. In spectral ID are determined anorthoclase, fayalite, hematite, bitovnite minerals. The REEs patterns of ignimbrites normalized to chondrite are similar each other. All of them show a decrease from high LREE to HREE. The LREE enrichment and La-n/Yb-n ratios (7.95-9.07) in ignimbrites is the sign of the liquid-rich calalkaline magmatic source. The cerium anomaly shows the decrease in solubility accompanying the oxidation of Ce (+3) to Ce (+4). The different color levels of ignimbrites can be summarized as cooling, iron oxide/iron hydroxides ratios (high in middle level), volatile elements (U,Th, Cl) (low in middle levell), devitrification of volcanic glass and chemical reactions. (C) 2020 Published by Elsevier B.V.
Keywords: Ignimbirite; Neutron activation analysis; CRSpectroscopy; Fayalite; Hematite; Easth Turkey